Effects of Phenolic Monomers on Enzymatic and Fermentation Activities of the Rumen Fungus, Neocallimastix Frontalis - Saad, Wan Zuhainis (2006)
The present study was undertaken to investigate the effects of phenolic monomers on the enzymes and fermentation activities of a rumen fungus, Neocallimastix frontalis, and to evaluate the ability of the fungus to colonize and degrade guinea grass which contained large amount of phenolic monomers. From 115 isolates of N. frontalis, 15 isolates of Piromyces mae and 3 isolates of Orpinomyces joyonii obtained from rumens of cattle and buffalo, a representative isolate of each species was selected for further studies on its cellulolytic activity. Neocallimastix frontalis B15, P. mae B6 and O. joyonii C3 were selected based on their good growth in straw and ball-milled filter paper media, and on their ability to maintain zoosporogenesis and viability in the subcultures. 14C-labelled bacterial (A. xylinum) cellulose was used to determine the cellulolytic activity of the three rumen fungal species and the effects of phenolic acids (ρ-coumaric and ferulic acids) on the activity. The results showed that N. frontalis B15 had the highest cellulolytic activity, and the phenolic acids had an inhibitory effect on the activity. Other N. frontalis strains isolated from buffalo (B9), cattle (C20) and goat were (G8) further characterized for their cellulolytic activities,and a strain, N. frontalis B9, which showed the highest activity was chosen for subsequent studies The enzymes produced by N. frontalis B9 grown in filter paper or guinea grass media included, CMCase, FPase, xylanase, β-glucosidase and β-xylosidase. The maximum production of all the enzymes was at 72 h of incubation. The activities of the enzymes in filter paper media in descending order were: CMCase > xylanase > FPase > β-glucosidase, and in guinea grass media were: xylanase > carboxymethylcellulase > FPase > β-xylosidase > β-glucosidase. Phenolic monomers were found to inhibit the production of the enzymes and fermentation activity of N. frontalis B9 in varying degrees. Of the four phenolic monomers, ρ-coumaric and ferulic acids were the most inhibitory and vanillin the least. The fermentation end-products were also inhibited by the phenolic monomers. Observations using scanning electron microscopy showed that N. frontalis B9 in control cultures without phenolic monomers could extensively colonise and degrade various tissues of guinea grass, but treatments with the phenolic monomers significantly reduced the colonization and degradation of the grass fragments. Phenolic monomers, particularly ρ-coumaric acid and ferulic acid also inhibited the dry weight loss and reduction in the textural strength of the grass fragments by N. frontalis B9, which indicated a reduction in the degradation of the grass fragments. Neocallimastix frontalis B9 produced esterases that released ferulic and ρ-coumaric acids from their methyl esters and guinea grass. Production of feruloyl and ρ-coumaroyl esterases, coupled with the penetrative ability provided by fungal rhizoids, provided a mechanism for the breakdown and subsequent utilization of the phenolic ester-linked carbohydrates present in plant cell walls.